Persepsi Guru Paud tentang Attention Deficit Hyperactivity Disorder (ADHD) pada Anak Usia Prasekolah (3-6 Tahun) - I Made Sudarma Adiputra; Ni Luh Ayu Yustikarini; A A Istri Dalem Hana Yundari; Ni Wayan Trisnadewi; Ni Putu Wiwik Oktaviani (Universitas Baiturrahim, 2021)
Attention Deficit Hyperactivity Disorder (ADHD) is a child who experiences obstacles in focusing attention, this condition is known as a hyperactive child term. PAUD teachers play an important role in ADHD child detection efforts, as teachers are often the first to see if their students have a keen behavioral difference when compared to other students. The study aims to get an overview of the Paud Teacher's perception of Attention Deficit Hyperactivity Disorder (ADHD) in preschool-aged children (3-6 years). This research uses qualitative research methods with a phenomenological approach. Data was obtained with an in-depth interview of 4 participants using the purposive sampling technique. The analysis used in this research is Colaizzi Analysis 7 step process. The results of the study getting five themes are facing the problem of ADHD children, planning problem solving, seeking support facing ADHD children, taking a positive meaning and accepting responsibility. Based on this research, it can be concluded that to optimize the child's growth, a teacher provides a special education in the form of wholeheartedly educating, patiently facing the child and giving more attention.